Age- and gender-related reference values of cardiac morphology and function in cardiovascular magnetic resonance - Riffel, Johannes; Mayo, Rebecca; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Katus, Hugo; André, Florian (The international journal of cardiovascular imaging, 2021)
Cardiovascular magnetic resonance (CMR) is the reference standard for the quantitative assessment of cardiac morphology and function. The aim of the study was to determine age- and gender-related reference values for cardiac morphology and function according to current recommendations. 454 healthy volunteers (235 men, median age 52.0 (44.0-59.0) years) underwent a standard CMR scan and were divided into six groups of nearly equal size with regard to sex (male, female) and age (21-47 years, 48-57 years, 58-84 years). Left ventricular end-diastolic (LV-EDV) and end-systolic (LV-ESV) volumes and LV mass (LV-M) were measured at end-diastole and end-systole in steady-state free precession series with including papillary muscles and trabecular tissue in the LV-M. Absolute and indexed volumetric parameters were significantly different between gender groups with higher values in men compared to women (all p < 0.001). Furthermore, a significant age-dependent decline could be observed for left ventricular and right ventricular volumes (all p < 0.001), while LV-M did not show differences between the different age-groups. Parameters of longitudinal function for the left and right ventricle were higher in female compared to male subjects with a significant age-dependent decline. We provided normal values for cardiac volumes, function, and mass derived in accordance with current guidelines from a large population of healthy subjects, which can be implemented in clinical routine as a standard of reference.